N-Adamantyl-4-methylthiazol-2-amine suppresses amyloid β-induced neuronal oxidative damage in cortical neurons. (2nd June 2016) - Cho, Chang Hun; Kim, Eun-A; Kim, Jiae; Choi, Soo Young; Yang, Seung-Ju; Cho, Sung-Woo
Abstract: Recently, we have reported that N -adamantyl-4-methylthiazol-2-amine (KHG26693) successfully reduced the production of oxidative stress in streptozotocin-induced diabetic rats and lipopolysaccharide-induced BV-2 microglial cells by increasing their antioxidant capacity. However, antioxidative effects of KHG26693 against Aβ (Aβ)-induced oxidative stress have not yet been reported. In the present study, we further investigated the antioxidative function of KHG26693 in Aβ-mediated primary cultured cortical neurons. We showed here that KHG26693 attenuated Aβ-induced cytotoxicity, increase of Bax/Bcl-2 ratio, elevation of caspase-3 expression, and impairment of mitochondrial membrane potential in cultured primary cortical neurons. KHG26693 also decreases the Aβ-mediated formation of malondialdehyde, reactive oxygen species, and NO production by decreasing nitric oxide synthase (iNOS) and NADPH oxidase level. Moreover, KHG26693 suppress the Aβ-induced oxidative stress through a possible mechanism involving attenuation of GSH and antioxidant enzyme activities such as glutathione reductase and glutathione peroxidase (GPx). Finally, pretreatment of cortical neurons with KHG26693 significantly reduced the Aβ-induced protein oxidation and nitration. To our knowledge, this is the first report, showing that KHG26693 significantly attenuates Aβ-induced oxidative stress in primary cortical neurons, and may prove attractive strategies to reduce Aβ-induced neural cell death.